Endotracheal suction in term non vigorous meconium stained neonates—A pilot study. (August 2016) - Nangia, Sushma; Sunder, Shyam; Biswas, Ratna; Saili, Arvind
Abstract: Aim: To evaluate the effect of 'No endotracheal suction' on occurrence of meconium aspiration syndrome (MAS) and/or all-cause mortality in non-vigorous neonates born through meconium stained amniotic fluid (MSAF). Methods: This pilot randomized controlled trial enrolled term non-vigorous neonates (≥37 weeks) born through MSAF. Neonates randomized to 'No Endotracheal suction group' ('No ET' Group; n  = 88) did not undergo endotracheal suction before the definitive steps of resuscitation. Neonates randomized to 'Endotracheal suction group' ('ET' Group; n  = 87) underwent tracheal suction as part of the initial steps as per the current NRP recommendations. The primary outcome was occurrence of MAS and/or death. Secondary outcome variables were duration and severity of respiratory distress, need for respiratory support, development of hypoxic ischemic encephalopathy (HIE) and duration of oxygen therapy and hospitalization. Results: Baseline characters including birth weight and gestational age were similar between the two groups. MAS was present in 23 (26.1%) vs. 28 (32.2%) neonates in 'No ET' and 'ET' groups respectively (OR 0.4 (0.12–1.4); p  = 0.14) with 4 (4.6%) and 9 (10.34%) deaths amongst these neonates with MAS in respective groups (OR 0.75 (0.62–1.2); p  = 0.38). Other parameters like severity and duration of respiratory distress, need for respiratory support, incidence of HIE, duration of oxygen therapy and duration of hospitalization were comparable. Conclusion: This study demonstrates that it is feasible to randomize non-vigorous infants born through meconium stained liquor to receive on not receive endotracheal suction. There is a need for a multi-center trial to address whether the current practices and guidelines can be justified.